Interpersonal styles and labor market outcomes - Lex Borghans; Bas ter Weel; Bruce A. Weinberg (Institute for the Study of Labor (IZA), 2006)
This paper develops a framework to understand the role of interpersonal interactions in the labor market including task assignment and wages. Effective interpersonal interactions involve caring, to establish cooperation, and at the same time directness, to communicate in an unambiguous way. The ability to perform these tasks varies with personality and the importance of these tasks varies across jobs. An assignment model shows that people are most productive in jobs that match their style and earn less when they have to shift to other jobs. An oversupply of one attribute relative to the other reduces wages for people who are better with the attribute in greater supply. We present evidence that youth sociability affects job assignment in adulthood. The returns to interpersonal interactions are consistent with the assignment model.
urn:nbn:de:101:1-2008060649
Keywords: 330; Soziale Beziehungen; Beruf; Kognition; Qualifikation; Lohnstruktur; Theorie